Jay Cooke correspondence - Cooke, Jay, 1821-1905.
ALS (1884 November 15) from Cooke with advice for a young man who requested an autograph and a sentiment.
Banker, financier, and fiscal agent for the U.S. Treasury Dept. during the Civil War.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Originally processed as part of the John Tyler Papers from which it was separated in 1997.
Keywords: Bankers; Financiers; Public officials